Data hiding exposing concealed data in multimedia, operating systems, mobile devices and network protocols - Raggo, Michael T. (Syngress, 2013)
As data hiding detection and forensic techniques have matured, people are creating more advanced stealth methods for spying, corporate espionage, terrorism, and cyber warfare all to avoid detection. Data Hiding provides an exploration into the present day and next generation of tools and techniques used in covert communications, advanced malware methods and data concealment tactics. The hiding techniques outlined include the latest technologies including mobile devices, multimedia, virtualization and others. These concepts provide corporate, goverment and military personnel with the knowledge to investigate and defend against insider threats, spy techniques, espionage, advanced malware and secret communications. By understanding the plethora of threats, you will gain an understanding of the methods to defend oneself from these threats through detection, investigation, mitigation and prevention. Review of the latest data hiding techniques presented at world-renownded conferencesProvides many real-world examples of data concealment on the latest technologies including iOS, Android, VMware, MacOS X, Linux and Windows 7Dives deep into the less known approaches to data hiding, covert communications, and advanced malwareIncludes never before published information about next generation methods of data hidingOutlines a well-defined methodology for countering threats. Looks ahead at future predictions for data hiding.